واقع استخدام تطبيقات ويب 2.0 في التعليم الطبي: دراسة ميدانية لأعضاء هيئة التدريس بجامعة المنيا - قناوي، يارة ماهر محمد (جامعة المنيا - كلية الآداب, 2016)
Aim and objectives of the study: The main aim of the research is to identify the usage of web 2.0 tools in medical education by medical staff at Minia University - Objectives: 1- Identify the concept of medicine 2.0 and study of the difference of medicine 2.0 and health 2.0. 2- Identify the extent use of staff social networking in the field of medicine. 3- Identify the problems and obstacles that limit the use of staff web 2.0 Application in medical Education. The Results of this study: 1- Facebook came first terms in medical education (22.7%), YouTube (68.2%) and Linked In (16.8%). 2- The reasons prevent using the information from web 2.0 tools it has non -authoritative information (75%)
Keywords: التطبيقات التكنولوجية -- التعليم الإلكترونى -- تطبيقات الويب 2.0 -- التعليم الطبى -- المدونات الإلكترونية -- أعضاء هيئة التدريس -- جامعة المنيا